The ethics of the comic in King Kong Fran: clowning, gender, and resistance - Santos, Maricélia Nunes dos (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2026)
This research focuses on the study of the dramaturgical text King Kong Fran (2023) by Rafaela Azevedo and Pedro Brício. The text, which originated from the show that is currently running in the theatrical circuits of Rio de Janeiro and São Paulo since late 2022, incorporates elements of circus and clowning to take a stand against social and artistic misogynistic practices. Considering the resources used in the construction of the work, I aim to identify the strategies of comedy and humor employed and to reflect on how these aesthetic choices are articulated with a political discourse concerning the confrontation of misogynistic structures and practices that affect women. To this end, I rely on the theoretical foundation provided by studies on comedy (Bakhtin, 1999; Bergson, 1980; Arêas, 1990, among others), as well as research that links the discussion of comedy and humor with feminist criticism (Acevedo, 2018; Avilano, 2021; Espinosa-Vera, 2010, among others). I observed that, via the strategies of mirroring and gender role reversal, using resources such as irony, parody, and exaggeration, the text is politically positioned as a denounce of the sexist practices that have historically marked artistic productions, especially in the contexts of circus and clowning, and the social life of women. I consider that the artistic corpus under study assumes an amphibious character (Santiago, 2004) by articulating aesthetics and politics in an ambivalent manner, aligning with what I call an ethics of the comic, as it proposes social transformation via laughter.